Mechanical properties of recycled steel fibre reinforced concrete - Lim, Lion Yee (2012)
Large quantities of scrap tires are generated each year globally. In Malaysia, huge quantities of scrap tires are produced every year resulting in environmental hazards. This paper discusses the feasibility of adding recycled steel fibre from scrap tires as reinforcement of normal concrete. A number of experimental tests were conducted to investigate slump, Ve-be time, compressive strength, splitting tensile strength, flexural strength and ultrasonic pulse velocity of recycled steel fibre reinforced concrete (RSFRC). The effect of the incorporation of various aspect ratios (l/d) and volume fraction (Vf) of recycled steel fibre were experimentally investigated. There were three different l/d ratios of 45, 67 and 89 were used. The compressive strength and splitting tensile strength of RSFRC reached a maximum at l/d ratio of 67. On the other hand, four different volumes fraction of recycled steel fibres (l/d ratio of 67) were added to concrete mixes at 0.5%, 1.0%, 1.5% and 2.0% by volume of concrete. The results indicated that the workability of RSFRC significantly reduced as the l/d ratio and volume fraction (Vf) of fibre increases. The compressive strength of RSFRC is not significant increases by incorporation of recycled steel fibre, being a 3.3% improvement over plain concrete at 2.0% volume fraction. The splitting tensile strength and flexural strength of RSFRC dramatically improved with increasing the volume fraction, achieving 148.6% and 51.7% improvement respectively, at 2.0% volume fraction. In addition, the results showed that the ultrasonic pulse velocity of RSFRC increased with the increase of the compressive strength. The experimental results suggest that the recycle steel fibre from waste tyre has potential to be used as reinforcing material in concrete.